The Norton anthology of theory and criticism - Leitch, Vincent B., 1944- (New York : W. W. Norton & Co., 2018)
The Norton Anthology of Theory and Criticism presents a staggeringly varied collection of the most influential critical statements from the classical era to the present day. Edited by scholars and teachers whose interests range from the history of poetics to postmodernism, from classical rhetoric to eriture feminine, and from the social construction of gender to the machinery of academic superstardom, The Norton Anthology of Theory and Criticism promises to become the standard anthology in its field. The Norton Anthology of Theory and Criticism offers nearly twice the number of selections in other leading anthologies and more twentieth-century selections than any other text (including anthologies devoted solely to the twentieth century). Edited by scholars and teachers whose interests range from the history of poetics to postmodernism, from classical rhetoric to eriture feminine, and from the social construction of gender to the machinery of academic superstardom, The Norton Anthology of Theory and Criticism promises to become the standard anthology in its field.
Includes bibliographical references and index.
Keywords: Criticism; Literature -- History and criticism -- Theory, etc